Benzylamine and Thenylamine Derived Drugs Induce Apoptosis and Reduce Proliferation, Migration and Metastasis Formation in Melanoma Cells - Mojena, Marina; Povo-Retana, Adrián; González-Ramos, Silvia; Fernández-García, Victoria; Regadera, Javier; Zazpe, Arturo; Artaiz, Inés; Martín-Sanz, Paloma; Ledo, Francisco; Boscá, Lisardo (Frontiers in Oncology, 2018)
Melanomas are heterogeneous and aggressive tumors, and one of the worse in prognosis. Melanoma subtypes follow distinct pathways until terminal oncogenic transformation. Here, we have evaluated a series of molecules that exhibit potent cytotoxic effects over the murine and human melanoma cell lines B16F10 and MalMe, respectively, both ex vivo and in animals carrying these melanoma cells. Ex vivo mechanistic studies on molecular targets involved in melanoma growth, migration and viability were evaluated in cultured cells treated with these drugs which exhibited potent proapoptotic and cytotoxic effects and reduced cell migration. These drugs altered the Wnt/β-catenin pathway, which is important for the oncogenic phenotype of melanoma cells. In in vivo experiments, male C57BL/6 or nude mice were injected with melanoma cells that rapidly expanded in these animals and, in some cases were able to form metastasis in lungs. Treatment with anti-tumor drugs derived from benzylamine and 2-thiophenemethylamine (F10503LO1 and related compounds) significantly attenuated tumor growth, impaired cell migration and reduced the metastatic activity. Several protocols of administration were applied, all of them leading to significant reduction in the tumor size and enhanced animal survival. Tumor cells carrying a luciferase transgene allowed a time-dependent study on the progression of the tumor. Molecular analysis of the pathways modified by F10503LO1 and related compounds defined the main relevant targets for tumor regression: the activation of pro-apoptotic and anti-proliferative routes. These data might provide the proof-of-principle and rationale for its further clinical evaluation.